Explorer les paysages alimentaires pour régénérer la fabrique agriurbaine - Jennifer Buyck; Aurore Meyfroidt (Territoire en Mouvement)
Through exploring foodscapes of the Grenoble metropolitan region, this paper aims at drawing a diagnosis of the agriurban model to highlight to what extent the food question tests this latter while providing prospective potentials. To do so, we ask here how taking into account food issues within agriurban contexts provides a renewal within contemporary urbanism - often mentioned as sustainable. This research was conducted through collective and prospective walks and informs us about agriurban foodscapes, their forms and systems of relations. It shows the disconnections between contemporary urbanism and inhabitants, their vital needs and more globally the soil, while fostering working hypothesis towards more “fertile”, “adaptive” and “embedded” agriurban fabrics. Considering agriurban through foodscapes we then contribute to the renewal of landscape thinking and thus we highlight propositions towards a development of tools and stakes of sustainable territorial planning. Could exploring foodscapes be a tool to “land” sustainable urbanism, especially within agriurban territories ?